Kendala Guru Dalam Pelaksanaan PTM Terbatas Pada Proses Kegiatan Belajar Mengajar - Ahmad Sururi; Diah Sunarsih; Didik Tri Setiyoko (Peneliti.net, 2022)
During the Covid-19 Pandemic, the government's obligation to provide education does not stop, the government is required to find certain ways so that the education process continues to run optimally. The government then took various kinds of policies by considering two things, on the one hand the education process must continue, but on the other hand the implementation of education should not cause or facilitate the rate of transmission of Covid-19, so the Limited PTM program was established. The purpose of this research is to (1) describe the constraints of teachers in the implementation of face-to-face learning which is limited to the teaching and learning process at SDN Pebatan 01 Wanasari Brebes (2) describe the solution to the constraints on implementing face-to-face learning which is limited to the teaching and learning process at SDN Pebatan 01 Wanasari Brebes. field research using a descriptive qualitative approach Data collection techniques using interviews, observation and documentation The validity of the data was carried out by technical triangulation techniques and source triangulation. n data collection, data reduction, data presentation and drawing conclusions. Based on the results of the study, it was concluded that the constraints of teachers in implementing PTM were limited to the process of teaching and learning activities, namely the delivery of materials was carried out in a limited manner, students did not fully understand the material presented, and students ignored health protocols. The solution applied by the teacher is to determine effective learning methods and make learning